Solar Cells

By increasing the molar ratio of fluorine atoms between the light absorption layer and the intermediate layer of the tin-based perovskite solar cell and reducing the tin defect density at the interface, the problem of low conversion efficiency of tin-based perovskite solar cell is solved and a higher conversion efficiency is achieved.

CN110544745BActive Publication Date: 2025-03-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201910421880.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-05-28
Filing Date
2019-05-21
Publication Date
2025-03-25
Estimated Expiration
2039-05-21

AI Technical Summary

Technical Problem

The existing tin-based perovskite solar cells have low conversion efficiency, mainly due to the high density of tin defects on the interface.

Method used

By forming an interface between the light absorbing layer and the intermediate layer, and increasing the molar ratio of fluorine atoms to more than 49% on the interface, the defect density on the interface is reduced.

Benefits of technology

The conversion efficiency of tin-based perovskite solar cells is significantly improved and the photoelectric conversion performance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110544745B_ABST
    Figure CN110544745B_ABST
Patent Text Reader

Abstract

The present disclosure provides a solar cell with high conversion efficiency. The solar cell disclosed in the present disclosure comprises: a light-transmitting first electrode; a second electrode; a light-absorbing layer located between the first electrode and the second electrode; and an intermediate layer located between the first electrode and the light-absorbing layer. The light-absorbing layer contains a fluorine compound and a perovskite compound represented by a composition formula ASnX3 (wherein A is a monovalent cation and X is a halogen anion). The intermediate layer contains at least one selected from metal oxides, metal sulfides, metal chalcogenides and metal nitrides. The upper surface of the intermediate layer contacts the lower surface of the light-absorbing layer. In the interface between the light-absorbing layer and the intermediate layer, the molar ratio of fluorine atoms to the perovskite compound is 49% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to solar cells. Background Art

[0002] In recent years, research and development of perovskite solar cells has been carried out. In perovskite solar cells, a perovskite compound represented by ABX3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) is used as a light absorbing material.

[0003] Non-patent document 1 discloses using a perovskite compound represented by CsSnI 3 as a light absorbing material of a perovskite solar cell, using TiO 2 as an electron transporting material, and using an organic semiconductor called Spiro-OMETAD as a hole transporting material.

[0004] Prior Art Literature

[0005] Non-patent document 1: Mulmudi Hemant Kumar, 12 others, "Lead-free halideperovskite solar cells with high photocurrents realized through vacancy modulation", Advanced Materials, (UK), November 2014, Vol. 26, No. 41, p. 7122-7127 Summary of the invention

[0006] Problems to be solved by the invention

[0007] The purpose of the present disclosure is to provide a tin-based perovskite solar cell with further improved conversion efficiency.

[0008] Means for solving problems

[0009] The solar cell involved in the present disclosure comprises:

[0010] A light-transmitting first electrode;

[0011] The second electrode;

[0012] a light absorbing layer located between the first electrode and the second electrode; and

[0013] an intermediate layer located between the first electrode and the light absorbing layer,

[0014] The light absorbing layer contains a fluorine compound and a perovskite compound represented by a composition formula ASnX3 (wherein A is a monovalent cation and X is a halogen anion),

[0015] The intermediate layer contains at least one selected from metal oxides, metal sulfides, metal chalcogenides and metal nitrides,

[0016] The upper surface of the intermediate layer is in contact with the lower surface of the light absorbing layer,

[0017] At the interface between the light absorbing layer and the intermediate layer, a molar ratio of fluorine atoms to the perovskite compound is 49% or more.

[0018] Effects of the Invention

[0019] The present disclosure provides a tin-based perovskite solar cell with further improved conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A cross-sectional view showing a solar cell according to a first embodiment of the present disclosure.

[0021] Figure 2 A cross-sectional view showing a solar cell according to a second embodiment of the present disclosure.

[0022] Figure 3 FIG. 4 is a cross-sectional view of a solar cell in which a hole having a depth d1 is formed in the light absorbing layer.

[0023] Description of Reference Numerals

[0024] 1 substrate

[0025] 2 1st electrode

[0026] 3 Light absorption layer

[0027] 4. Second electrode

[0028] 5 Electron transport layer

[0029] 6 Hole Transport Layer

[0030] 7 Middle Layer

[0031] 100 Solar Cells DETAILED DESCRIPTION

[0032] <Definition of terms>

[0033] The term "perovskite compound" used in this specification refers to a perovskite crystal structure represented by the chemical formula ABX3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) and a crystal structure having a similar structure thereto.

[0034] The term "tin-based perovskite compound" used in this specification refers to a perovskite compound containing tin.

[0035] The term "tin-based perovskite solar cell" used in this specification refers to a solar cell including a tin-based perovskite compound as a light absorbing material.

[0036] (Embodiments of the present disclosure)

[0037] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0038] (First embodiment)

[0039] Figure 1 1 is a cross-sectional view of a solar cell 100 according to the first embodiment. Figure 1 As shown, the solar cell 100 according to the first embodiment includes a first electrode 2 , a second electrode 4 , a light absorbing layer 3 , and an intermediate layer 7 .

[0040] The light absorbing layer 3 is located between the first electrode 2 and the second electrode 4. The first electrode 2 is opposite to the second electrode 4 in a manner that the light absorbing layer 3 is arranged between the first electrode 2 and the second electrode 4. The first electrode 2 has light transmittance. In this specification, "the electrode has light transmittance" means that more than 10% of light with a wavelength of 200 nm or more and 2000 nm or less passes through the electrode at any wavelength.

[0041] The intermediate layer 7 is located between the first electrode 2 and the light absorbing layer 3 .

[0042] Figure 1 The solar cell 100 shown further includes a substrate 1, an electron transport layer 5, and a hole transport layer 6. The solar cell 100 may not include the substrate 1. The electron transport layer 5 is located between the intermediate layer 7 and the light absorbing layer 3. As described in the second embodiment, the intermediate layer 7 may also serve as the electron transport layer 5. The hole transport layer 6 is located between the light absorbing layer 3 and the second electrode 4. The solar cell 100 may not include the hole transport layer 6.

[0043] Since the first electrode 2 has light-transmitting properties, light passes through the first electrode 2 and reaches the light-absorbing layer 3 .

[0044] (Light absorbing layer 3)

[0045] The light absorbing layer 3 contains a perovskite compound represented by the chemical formula ASnX3 (wherein A is a monovalent cation and X is a halogen anion) as a light absorbing material. The monovalent cation located at the A site is not limited. Examples of monovalent cations include organic cations or alkali metal cations. Examples of organic cations include methylammonium cations (i.e., CH3NH3 + ), formamidinium cation (i.e. NH2CHNH2 + ), phenylethylammonium cation (i.e. C6H5CH2CH2NH3 + ) or guanidinium cation (i.e. CH6N3+ Examples of alkali metal cations include cesium cations (Cs + ). The monovalent cation at the A site is preferably a carboxamidinium cation. The monovalent cation at the A site may be composed of two or more cations. An example of a halogen anion at the X site is an iodide ion. The halogen anion at the X site may be composed of two or more halogen ions.

[0046] The light absorbing layer 3 further contains a fluorine compound. The fluorine compound is not limited. Examples of fluorine compounds include metal fluorides. Examples of metal fluorides include SnF2, SnF4, MgF, NaF or KF.

[0047] As described above, the light absorbing layer 3 contains a perovskite compound represented by the chemical formula ASnX3 and a fluorine compound. “The light absorbing layer 3 contains a perovskite compound represented by the chemical formula ASnX3” includes that the light absorbing layer 3 contains 70% by mass or more of the perovskite compound represented by the chemical formula ASnX3. For example, the light absorbing layer 3 may contain 80% by mass or more of the perovskite compound. The light absorbing layer 3 may contain impurities. The light absorbing layer 3 may also contain compounds other than the perovskite compound represented by the chemical formula ASnX3 and the fluorine compound.

[0048] The thickness of the light absorbing layer 3 is, for example, 100 nm to 10 μm. Alternatively, the thickness of the light absorbing layer 3 may be 100 nm to 1000 nm. The thickness of the light absorbing layer 3 depends on the light absorption of the light absorbing layer 3. The light absorbing layer 3 may be formed by a coating method using a solution.

[0049] (Middle layer 7)

[0050] The intermediate layer 7 contains a metal oxide, a metal sulfide, a metal chalcogenide or a metal nitride.

[0051] Examples of metal oxides include oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si or Cr. TiO2 is preferred.

[0052] Other examples of metal oxides are perovskite oxides. Examples of perovskite oxides are SrTiO3 or CaTiO3.

[0053] Examples of metal sulfides are CdS, ZnS, In2S3, SnS, PbS, Mo2S, WS2, Sb2S3, Bi2S3, ZnCdS2 or Cu2S.

[0054] Examples of metal chalcogenides are CdSe, CsSe, In2Se3, WSe2, HgSe, SnSe, PbSe or CdTe. The term "chalcogenide" in this specification refers to a selenide or a telluride.

[0055] Examples of metal nitrides are GaN or TaN.

[0056] The thickness of the intermediate layer 7 can be greater than 0.01 μm and less than 10 μm, or greater than 0.1 μm and less than 1 μm. The surface roughness of the intermediate layer 7 can be relatively large. Specifically, the surface roughness coefficient given by the effective area / projected area can be greater than 10, or greater than 100. Furthermore, the projected area refers to the area of ​​the shadow formed at the rear when light is irradiated to the object from the front. The effective area refers to the actual surface area of ​​the object. The effective area can be calculated based on the volume calculated from the projected area and thickness of the object, and the specific surface area and volume density of the material constituting the object. The specific surface area is measured, for example, by the nitrogen adsorption method.

[0057] In the solar cell 100 according to the first embodiment, an interface 3a is formed between the light absorbing layer 3 and the intermediate layer 7. More specifically, the lower surface of the light absorbing layer 3 and the upper surface of the intermediate layer 7 are in contact with each other. An interface 3a is formed therebetween. The light absorbing layer 3 has two main surfaces (i.e., an upper surface and a lower surface). The lower surface of the light absorbing layer 3 refers to the main surface in contact with the intermediate layer 7 (i.e., the main surface opposite to the first electrode 2). Similarly, the intermediate layer 7 also has two main surfaces (i.e., an upper surface and a lower surface). The upper surface of the intermediate layer 7 refers to the main surface in contact with the light absorbing layer 3 (i.e., the main surface opposite to the second electrode 4).

[0058] In the solar cell 100 according to the first embodiment, the molar ratio of fluorine atoms to the perovskite compound on the interface 3 a is a high value of 0.49 or more.

[0059] The molar ratio is calculated based on the following formula (1) from the measurement results obtained by X-ray photoelectron spectroscopy (hereinafter referred to as "XPS method").

[0060] Molar ratio = (the number of moles of fluorine atoms in the interval d2) / {(the number of moles of halogen anions (eg, iodine ions) contained in the perovskite compound in the light absorbing layer 3) / 3} (1)

[0061] like Figure 3As shown, a hole 3h with a depth of d1 is formed in the light absorbing layer 3 by etching, and then the composition of elements contained in the interval d2 is measured using an X-ray photoelectron spectrometer. The interval d2 is the distance between the bottom b1 of the hole 3h and a position b2 deeper than the bottom b1. When measuring the molar ratio on the interface 3a, the depth d1 is approximately equal to the thickness of the light absorbing layer 3. The value of the interval d2 depends on the performance of the X-ray photoelectron spectrometer.

[0062] For the detailed method of calculating the molar ratio, please refer to the Examples described below.

[0063] A high molar ratio of 0.49 or more means that the defect density of tin on the interface 3a is low. Therefore, the solar cell 100 of the first embodiment has a higher conversion efficiency than conventional perovskite solar cells.

[0064] The molar ratio may be 0.75 or less. The molar ratio may be 0.502 or more and 0.663 or less. A solar cell having such a molar ratio has a higher conversion efficiency than a conventional perovskite solar cell.

[0065] The intermediate layer 7 may be porous. In other words, the intermediate layer 7 may be formed of a porous body. Examples of the porous body include a porous body in which a plurality of particles formed of the above-mentioned metal oxide, metal sulfide or metal chalcogenide are connected to each other.

[0066] The pores contained in the intermediate layer 7 formed by the porous body are connected from the portion in contact with the first electrode 2 to the portion in contact with the electron transport layer 5. The material of the light absorbing layer 3 is filled in the pores contained in the intermediate layer 7. In other words, the pores are filled with at least one of the perovskite compound and the fluorine compound represented by the chemical formula ASnX3. The pores can also be filled with both the perovskite compound and the fluorine compound. Since the first electrode 2 is in contact with the electron transport layer 5, the electrons move directly from the electron transport layer 5 to the first electrode 2.

[0067] Light is scattered by the porous intermediate layer 7. Therefore, the optical path length of light passing through the light absorbing layer 3 can be increased. The increase in the optical path length can increase the amount of electrons and holes generated in the light absorbing layer 3.

[0068] The intermediate layer 7 does not hinder the light absorption of the light absorbing layer 3 . The intermediate layer 7 does not hinder the movement of electrons from the light absorbing layer 3 to the electron transporting layer 5 .

[0069] (Substrate 1)

[0070] The substrate 1 holds the first electrode 2, the electron transport layer 5, the light absorbing layer 3, and the second electrode 4. The substrate 1 can be formed of a transparent material. Examples of the substrate 1 include a glass substrate or a plastic substrate. Examples of the plastic substrate include a plastic film. When the first electrode 2 has sufficient strength, the first electrode 2 holds the electron transport layer 3, the light absorbing layer 4, and the second electrode 4, so the solar cell 100 does not need to have the substrate 1.

[0071] (First electrode 2 and second electrode 4)

[0072] The first electrode 2 has conductivity and light transmittance. The second electrode 4 has conductivity. The second electrode 4 may also have light transmittance. Light in the visible region to the near-infrared region can pass through the first electrode 2. The second electrode 4 may also be configured to allow light in the visible region to the near-infrared region to pass through.

[0073] The first electrode 2 and the second electrode 4 are each formed using, for example, at least one of a transparent and conductive metal oxide and a metal nitride.

[0074] Examples of metal oxides are

[0075] (i) titanium oxide doped with at least one selected from lithium, magnesium, niobium and fluorine,

[0076] (ii) gallium oxide doped with at least one selected from tin and silicon,

[0077] (iii) indium-tin composite oxide,

[0078] (iv) tin oxide doped with at least one selected from antimony and fluorine,

[0079] (v) Zinc oxide doped with at least one selected from boron, aluminum, gallium and indium.

[0080] A composite composed of two or more metal oxides may also be used.

[0081] An example of the metal nitride is gallium nitride doped with at least one selected from silicon and oxygen. Two or more metal nitrides may be used in combination.

[0082] Metal oxides and metal nitrides may be used in combination.

[0083] The first electrode 2 can be formed by setting a light-transmitting pattern using an opaque material. As the light-transmitting pattern, for example, a linear, wavy line, a lattice, and a punched metal pattern formed by regular or irregular arrangement of a plurality of fine through holes can be cited. If the first electrode 2 has these patterns, light can be transmitted through the portion where the electrode material is not present. As the opaque material, for example, platinum, gold, silver, copper, aluminum, rhodium, indium, titanium, iron, nickel, tin, zinc, and an alloy containing any of these metals can be cited. In addition, a conductive carbon material can also be used.

[0084] In the case where the solar cell 100 does not have a hole transport layer 6, the second electrode 4 is formed of, for example, a material having a blocking property for electrons from the light absorption layer 3. In this case, the second electrode 4 is not in ohmic contact with the light absorption layer 3. The blocking property for electrons from the light absorption layer 3 refers to the property of only allowing holes generated in the light absorption layer 3 to pass through and not allowing electrons to pass through. The Fermi level of a material having such a property is lower than the energy level at the bottom of the conduction band of the light absorption layer 3. The Fermi level of the above-mentioned material may be lower than the Fermi level of the light absorption layer 3. Examples of such materials include carbon materials such as platinum, gold, or graphene. In the case where the solar cell 100 has a hole transport layer 6, the second electrode 4 may not have a blocking property for electrons from the light absorption layer 3.

[0085] The material having a barrier property against electrons from the light absorbing layer 3 may not have a light-transmitting property. Therefore, when the second electrode 4 is formed of such a material, the second electrode 4 has the above-mentioned pattern for allowing light to pass through the second electrode 4 .

[0086] The light transmittance of each of the first electrode 2 and the second electrode 4 may be, for example, 50% or more, or 80% or more. The wavelength of the transmitted light depends on the absorption wavelength of the light absorbing layer 3. The thickness of each of the first electrode 2 and the second electrode 4 is, for example, 1 nm or more and 1000 nm or less.

[0087] (Electron Transport Layer 5)

[0088] The electron transport layer 5 is a dense layer containing a semiconductor. The semiconductor has a band gap of 3.0 eV or more. When the electron transport layer 5 contains a semiconductor having a band gap of 3.0 eV or more, visible light and infrared light reach the light absorbing layer 3. Examples of semiconductors include organic or inorganic n-type semiconductors.

[0089] Examples of organic n-type semiconductors include imide compounds, quinone compounds, fullerenes or fullerene derivatives. Examples of inorganic n-type semiconductors include metal oxides, metal nitrides or perovskite oxides. Examples of metal oxides include oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si or Cr. TiO2 is preferred. Examples of metal nitrides include GaN. Examples of perovskite oxides include SrTiO3 or CaTiO3.

[0090] The electron transport layer 5 may contain a substance having a band gap greater than 6.0 eV. Examples of substances having a band gap greater than 6.0 eV include (i) halides of alkali metals or alkaline earth metals such as lithium fluoride or calcium fluoride, (ii) alkali metal oxides such as magnesium oxide, or (iii) silicon dioxide. In this case, in order to ensure the electron transport property of the electron transport layer 5, the thickness of the electron transport layer 5 is, for example, less than 10 nm.

[0091] The electron transport layer 5 may include a plurality of layers formed of different materials.

[0092] (Hole Transport Layer 6)

[0093] The hole transport layer 6 is composed of an organic substance or an inorganic semiconductor. Representative examples of organic substances used for the hole transport layer 6 include 2,2',7,7'-tetrakis-(N,N-di-p-methoxyaniline)9,9'-spirobifluorene (hereinafter referred to as "spiro-OMeTAD"), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (hereinafter referred to as "PTAA"), poly(3-hexylthiophene-2,5-diyl) (hereinafter referred to as "P3HT"), poly(3,4-ethylenedioxythiophene) (hereinafter referred to as "PEDOT"), or copper phthalocyanine (hereinafter referred to as "CuPC").

[0094] Examples of inorganic semiconductors are Cu2O, CuGaO2, CuSCN, CuI, NiO x 、MoO x , V2O5 or carbon materials such as graphene oxide.

[0095] The hole transport layer 6 may include a plurality of layers formed of different materials.

[0096] The thickness of the hole transport layer 6 may be greater than 1 nm and less than 1000 nm, may be greater than 10 nm and less than 500 nm, or may be greater than 10 nm and less than 50 nm. If the thickness of the hole transport layer 6 is greater than 1 nm and less than 1000 nm, sufficient hole transport properties can be exhibited. In addition, if the thickness of the hole transport layer 6 is greater than 1 nm and less than 1000 nm, since the resistance of the hole transport layer 6 is low, light can be converted into electricity with high efficiency.

[0097] The hole transport layer 6 may contain a supporting electrolyte and a solvent. The supporting electrolyte and the solvent stabilize the holes in the hole transport layer 6 .

[0098] Examples of supporting electrolytes include ammonium salts or alkali metal salts. Examples of ammonium salts include tetrabutylammonium perchlorate, tetraethylammonium hexafluorophosphate, imidazolium salts or pyridinium salts. Examples of alkali metal salts include lithium bis(trifluoromethanesulfonyl)imide (hereinafter referred to as "LiTFSI"), LiPF6, LiBF4, lithium perchlorate or potassium boron tetrafluoride.

[0099] The solvent contained in the hole transport layer 6 may have high ion conductivity. The solvent may be an aqueous solvent or an organic solvent. From the viewpoint of stabilization of the solute, an organic solvent is preferred. Examples of organic solvents include heterocyclic compounds such as tert-butylpyridine, pyridine, or n-methylpyrrolidone.

[0100] The solvent contained in the hole transport layer 6 may be an ionic liquid. The ionic liquid may be used alone or in a mixture with other solvents. The ionic liquid is preferred in terms of low volatility and high flame retardancy.

[0101] Examples of the ionic liquid include imidazole compounds such as 1-ethyl-3-methylimidazolium tetracyanoborate, pyridine compounds, alicyclic amine compounds, aliphatic amine compounds, or azoamine compounds.

[0102] The position of the electron transport layer 5 and the position of the hole transport layer 6 may be interchanged.

[0103] (Basic Functions and Effects of Solar Cell 100)

[0104] Next, the basic effects of the solar cell 100 are described. When the solar cell 100 is irradiated with light, the light absorbing layer 3 absorbs the light and generates excited electrons and holes. The excited electrons move to the electron transport layer 5. On the other hand, the holes generated in the light absorbing layer 3 move to the hole transport layer 6. As described above, the electron transport layer 5 and the hole transport layer 6 are in electrical contact with the first electrode 2 and the second electrode 4, respectively, so that current is extracted from the first electrode 2 and the second electrode 4, which function as the negative electrode and the positive electrode, respectively.

[0105] <Foundation that forms the basis of this disclosure>

[0106] The findings that form the basis of the present disclosure will be described.

[0107] In theory, tin-based perovskite solar cells have high conversion efficiency. However, due to the high defect density of tin-based perovskite compounds, the conversion efficiency of tin-based perovskite solar cells is actually low. Non-patent document 1 discloses that the reason for the low conversion efficiency of tin-based perovskite solar cells is due to the high defect density of tin in the tin-based perovskite compound. In addition, non-patent document 1 discloses that tin fluoride is used as a dopant to reduce the defect density of tin in the tin-based perovskite compound. If a tin-based perovskite compound is modulated using a solution containing a precursor of the tin-based perovskite compound and tin fluoride, the defect density of tin in the tin-based perovskite compound will be reduced.

[0108] The conversion efficiency of tin-based perovskite solar cells is closely related to the defect density of tin on the interface between the light absorbing layer containing the tin-based perovskite compound and the layer adjacent to the light absorbing layer. In order to increase the conversion efficiency of tin-based perovskite solar cells, it is necessary to reduce the defect density on the interface. However, there is a limit to reducing the defect density of tin on the interface between the light absorbing layer and the layer adjacent to the light absorbing layer by using a method containing a precursor of a tin-based perovskite compound and a solution of tin fluoride. Since tin fluoride is an insulator, when the concentration of tin fluoride in the light absorbing layer is too high, there is a problem that tin fluoride hinders the transport of electrons or holes in the light absorbing layer.

[0109] As described above, if the defect density on the interface 3a between the light absorbing layer 3 and the intermediate layer 7 is further reduced, the conversion efficiency of the tin-based perovskite solar cell is further improved. In the present disclosure, as confirmed in the examples described later, the molar ratio of fluorine atoms on the interface 3a to the perovskite compound is made 49% or more, so the defect density on the interface 3a is reduced. As a result, the solar cell 100 of the present disclosure has a high conversion efficiency.

[0110] (Method of Manufacturing Solar Cell 100)

[0111] The solar cell 100 can be manufactured, for example, by the following method: First, the first electrode 2 is formed on the surface of the substrate 1 by chemical vapor deposition (hereinafter referred to as "CVD") or sputtering. Then, the electron transport layer 5 is formed on the first electrode 2 by sputtering.

[0112] Next, the intermediate layer 7 is formed on the electron transport layer 5 .

[0113] The intermediate layer 7 is formed on the electron transport layer 5. First, a powder of a metal oxide, a metal sulfide or a metal chalcogenide is dispersed in a dispersion solvent to prepare a paste. An example of a dispersion solvent is ethyl cellulose. The prepared paste is applied to the electron transport layer 5 by a coating method, and then the intermediate layer 7 is formed by firing.

[0114] The intermediate layer 7 formed of a porous body makes it easy to form the light absorbing layer 3. The material of the light absorbing layer 3 enters the pores of the intermediate layer 7. Therefore, the possibility of the material of the light absorbing layer 3 being repelled or agglomerated on the surface of the intermediate layer 7 formed of a porous body is reduced. Therefore, the intermediate layer 7 becomes a foothold of the light absorbing layer 3, and the light absorbing layer 3 can be formed into a uniform film. The light absorbing layer 3 can be formed by applying a solution on the intermediate layer 7 by a spin coating method and heating it.

[0115] The light absorbing layer 3 can be formed by the following method. As an example, the light absorbing layer 3 is formed by the following method. 1-x (C6H5CH2CH2NH3) x SnI3 (where 0<x<1, hereinafter sometimes referred to as “FA 1-x PEA x The method for forming the light absorbing layer 3 of the perovskite compound represented by SnI3”) and the fluorine compound is described.

[0116] First, a fluorine compound is added to a first organic solvent to obtain a first solution. Examples of the first organic solvent include alcohols such as butanol, ethers such as diethyl ether, lactones, alkyl sulfoxides such as dimethyl sulfoxide (hereinafter referred to as "DMSO"), or amides such as N,N-dimethylformamide (hereinafter referred to as "DMF"). Two or more first organic solvents may be mixed and used.

[0117] Next, the first solution is applied to the intermediate layer 7 by spin coating to form a coating film. The formed coating film is heated at a temperature of 75 degrees Celsius or more and 85 degrees Celsius or less for 25 minutes or more and 35 hours or less using a heating device such as a hot plate. Thus, a fluorine compound layer is formed. A portion of the first solution enters the interior of the intermediate layer 7 formed by the porous body, but the first solution is also formed on the intermediate layer 7, and then solidified to form a fluorine compound layer covering the upper surface of the intermediate layer 7. The thickness of the fluorine compound layer is, for example, 5 nm or more and 15 nm or less.

[0118] Then, SnI2, SnF2, HC(NH2)2I (hereinafter referred to as "FAI") and C6H5CH2CH2NH3I (hereinafter referred to as "PEAI") are added to the second organic solvent to obtain a second solution. An example of the second organic solvent is a mixed solution of DMSO and DMF (DMSO:DMF=1:1 (volume ratio)).

[0119] The molar concentration of SnI2 may be greater than or equal to 0.8 mol / L and less than or equal to 2.0 mol / L, or may be greater than or equal to 0.8 mol / L and less than or equal to 1.5 mol / L.

[0120] The molar concentration of SnF2 may be greater than or equal to 0.01 mol / L and less than or equal to 1.0 mol / L, or may be greater than or equal to 0.01 mol / L and less than or equal to 0.5 mol / L.

[0121] The molar concentration of FAI may be 0.8 mol / L or more and 2.0 mol / L or less, or 0.8 mol / L or more and 1.5 mol / L or less.

[0122] The molar concentration of PEAI may be 0.1 mol / L or more and 0.3 mol / L or less, or 0.1 mol / L or more and 0.5 mol / L or less.

[0123] Next, the second solution is heated to a temperature of 40 degrees Celsius or higher and 180 degrees Celsius or lower using a heating device. Thus, a mixed solution in which SnI2, SnF2, FAI and PEAI are dissolved is obtained. The obtained mixed solution is then left at room temperature.

[0124] The mixed solution is applied on the fluorine compound layer by spin coating to form a coating film. Then, the coating film is heated at a temperature of more than 40 degrees Celsius and less than 100 degrees Celsius for more than 15 minutes and less than 1 hour. In this way, the light absorbing layer 3 can be obtained. In the case of applying the mixed solution by spin coating, a poor solvent can be added dropwise during the spin coating. Examples of poor solvents include toluene, chlorobenzene or diethyl ether. The fluorine compound (such as SnF2) contained in the fluorine compound layer is dissolved or dispersed in the mixed solution. Therefore, a concentration gradient of the fluorine compound is formed in the mixed solution applied on the fluorine compound layer. As a result, a concentration gradient of the fluorine compound is formed in the light absorbing layer 3 in a manner that the concentration of the fluorine compound gradually decreases in the direction from the lower part of the light absorbing layer 3 to the upper part (that is, from the intermediate layer 7 to the second electrode 4). In other words, the concentration of the fluorine compound is high in the lower part of the light absorbing layer 3, and the concentration of the fluorine compound is low in the upper part of the light absorbing layer 3. Thus, at the interface 3a, the molar ratio of fluorine atoms relative to the perovskite compound represented by the chemical formula ASnX3 increases.

[0125] The second solution may contain a quenching substance such as tin fluoride. The concentration of the quenching substance may be 0.05 mol / L or more and 0.4 mol / L or less. The quenching substance suppresses the generation of defects in the light absorbing layer 3. The reason for the generation of defects in the light absorbing layer 3 may be, for example, due to Sn4 + The amount of Sn increases, which increases the Sn pores.

[0126] A hole transport layer 6 is formed on the light absorbing layer 3. Examples of methods for forming the hole transport layer 6 include coating and printing. Examples of coating methods include blade coating, rod coating, spray coating, dip coating, or spin coating. Examples of printing methods include screen printing. The hole transport layer 6 may be formed by mixing a plurality of materials, and then the hole transport layer 6 may be pressurized or fired. In the case where the hole transport layer 6 is formed of an organic low molecular weight substance or an inorganic semiconductor, the hole transport layer 6 may be formed by vacuum evaporation.

[0127] Next, the second electrode 4 is formed on the hole transport layer 6. In this way, the solar cell 100 is obtained. The second electrode 4 can be formed by chemical vapor deposition or sputtering.

[0128] (Second embodiment)

[0129] Figure 2 A cross-sectional view of a solar cell 100 according to the second embodiment is shown. In the second embodiment, the intermediate layer 7 is an electron transport layer 5 formed of a dense layer. In other words, the electron transport layer 5 also serves as the intermediate layer 7. In the second embodiment, the electron transport layer 5 is formed of a metal oxide. The electron transport layer 5 also serving as the intermediate layer 7 is preferably formed of TiO2.

[0130] (Example)

[0131] The present disclosure is described in more detail with reference to the following examples.

[0132] [Example 1]

[0133] (Fabrication of Perovskite Solar Cells)

[0134] In Example 1, the following preparation was performed Figure 1 A perovskite solar cell 200 is shown.

[0135] A glass substrate (manufactured by Nippon Sheet Glass Co., Ltd.) having an indium-doped SnO2 layer on its surface was prepared. The glass substrate and the SnO2 layer respectively functioned as a substrate 1 and a first electrode 2. The glass substrate had a thickness of 1 mm.

[0136] On the first electrode 2 , a titanium oxide layer having a thickness of about 10 nm was formed as the electron transport layer 5 by sputtering.

[0137] Next, a high-purity titanium oxide powder having an average primary particle size of 30 nm was dispersed in ethyl cellulose to prepare a titanium oxide paste.

[0138] The prepared titanium oxide paste was applied onto the electron transport layer 5 by screen printing and then dried. The titanium oxide paste was fired at 500 degrees Celsius for 30 minutes in air to form the intermediate layer 7 consisting of a porous titanium oxide layer with a thickness of 200 nm.

[0139] Next, in a glove box filled with N2, a DMSO solution (80 μl) containing SnF2 is dripped onto the intermediate layer 7, and the DMSO solution is applied to the intermediate layer 7 by spin coating, thereby forming a coating film. The oxygen concentration in the glove box is below 0.1 ppm. The DMSO solution has a SnF2 concentration of 0.1 mol / L. The coating film is heated on a hot plate maintained at 80 degrees Celsius, thereby forming a layer containing SnF2 (i.e., a fluorine compound layer). The pores of the porous titanium oxide partially contain SnF2.

[0140] Then, SnI2, SnF2, FAI (i.e., HC(NH2)2I) and PEAI (i.e., C6H5CH2CH2NH3I) were added to a mixed solvent of DMSO and DMF to obtain a mixed solution. The volume ratio of DMSO:DMF in the mixed solvent was 1:1. The concentrations of SnI2, SnF2, FAI and PEAI in the mixed solution were 1.5 mol / L, 0.15 mol / L, 1.5 mol / L and 0.3 mol / L, respectively.

[0141] In a glove box, the mixed solution (80 μl) was applied to the fluorine compound layer by spin coating to obtain a coating film with a thickness of 300 nm. Then, the coating film was heated on a hot plate maintained at 80 degrees Celsius. In this way, a light absorption layer 3 with a thickness of 300 nm was formed. The light absorption layer 3 mainly contained a chemical formula of FA 0.83 PEA 0.17 Perovskite compound of SnI3.

[0142] Then, in a glove box, a toluene solution (80 μl) containing PTAA (i.e., poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) at a concentration of 10 mg / ml was applied on the light absorbing layer 3 by spin coating to form a hole transport layer 6 with a thickness of 10 nm.

[0143] Finally, gold was deposited to a thickness of 100 nm on the hole transport layer 6 to form the second electrode 4. In this way, the solar cell of Example 1 was obtained.

[0144] (Determination of molar ratio)

[0145] For the solar cell of Example 1, the molar ratio of fluorine atoms to the perovskite compound at the interface 3 a between the light absorbing layer 3 and the intermediate layer 7 was measured by the following method.

[0146] First, the light absorbing layer 3 is etched in the thickness direction of the light absorbing layer 3 starting from the second electrode 4, and the elemental composition of the etched light absorbing layer 3 is measured by the XPS method (i.e., X-ray photoelectron spectroscopy) using an X-ray photoelectron spectroscopy measuring device (produced by ULVAC-PHI Co., Ltd., product name: PHI5000VersaProbe).

[0147] like Figure 3 As shown, a hole 3h with a depth of d1 is formed in the light absorbing layer 3 by etching. The composition of the elements contained in the interval d2 is measured by an X-ray photoelectron spectrometer. The interval d2 is the distance between the bottom b1 of the hole 3h and a position b2 deeper than the bottom b1. In the X-ray photoelectron spectrometer used in this embodiment, the interval d2 (i.e., the depth d2) is 10nm. In other words, the X-ray photoelectron spectrometer used in this embodiment has a spectral capability of 10nm.

[0148] The etching was performed by a sputtering method using argon gas.

[0149] The X-ray source is Al.

[0150] X-rays are monochromatized.

[0151] The output of X-rays is 24.8W.

[0152] Using the measured elemental composition, the molar ratio of fluorine atoms to the perovskite compound at the depth d1 was calculated based on the following formula (2).

[0153] Molar ratio = (the number of moles of fluorine atoms in the interval d2) / {(the number of moles of iodine ions contained in the perovskite compound contained in the light absorbing layer 3) / 3} (2)

[0154] As described above, the thickness of the light absorbing layer 3 is 300 nm. Therefore, the molar ratio when the depth d1 is 300 nm is the molar ratio of fluorine atoms to the perovskite compound at the interface 3 a between the light absorbing layer 3 and the intermediate layer 7 .

[0155] (Determination of conversion efficiency)

[0156] The solar cell of Example 1 was irradiated with 100 mW / cm 2 The conversion efficiency of the solar cell of Example 1 was measured using simulated sunlight with an illumination of .

[0157] [Example 2]

[0158] In Example 2, the same experiment as in Example 1 was conducted except for the following item (i).

[0159] (i) The DMSO solution containing SnF2 has a SnF2 concentration of 0.3 mol / L.

[0160] [Example 3]

[0161] In Example 3, the same experiment as in Example 1 was conducted except for the following item (i).

[0162] (i) The DMSO solution containing SnF2 has a SnF2 concentration of 0.7 mol / L.

[0163] [Example 4]

[0164] In Example 4, the same experiment as in Example 1 was carried out except for the following item (i).

[0165] (i) The DMSO solution containing SnF2 has a SnF2 concentration of 1.0 mol / L.

[0166] [Comparative Example 1]

[0167] In Comparative Example 1, the same experiment as in Example 1 was conducted except for the following item (i).

[0168] (i) The DMSO solution containing SnF 2 was not dropped onto the intermediate layer 7 .

[0169] Tables 1 and 2 show the results obtained in Examples 1 to 4 and Comparative Example 1.

[0170] Table 1

[0171]

[0172] Table 2

[0173] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Conversion efficiency (%) 4.11 4.34 4.16 3.96 3.68

[0174] It can be seen from Tables 1 and 2 that as the concentration of SnF2 in the DMSO solution increases, the molar ratio increases.

[0175] In the solar cells of Examples 1 to 4, the molar ratio at the interface 3a (ie, the molar ratio at a depth d1 of 300 nm) is 0.49 or more, and therefore the solar cells of Examples 1 to 4 have higher conversion efficiencies than the solar cell of Comparative Example 1.

[0176] The present inventors believe that in the solar cells of Examples 1 to 4, the Sn pores in the perovskite compound contained in the light absorbing layer 3 are replaced by SnF 2 , thereby increasing the conversion efficiency.

[0177] On the other hand, by comparing Examples 1 and 2 with Examples 3 and 4, it can be seen that the conversion efficiency decreases as the molar ratio at the interface 3a increases significantly.

[0178] The present inventors believe that the reason why the conversion efficiency is reduced is that (i) SnF 2 is an insulator and (ii) SnF 2 inhibits the movement of electrons or holes in the light absorbing layer 3 .

[0179] As can be seen from Tables 1 and 2, when the molar ratio at the interface 3a is 0.502 or more and 0.663 or less, the solar cell has a particularly high conversion efficiency of 4.11% or more.

[0180] Industrial Availability

[0181] The solar cell disclosed in the present invention can be used as a solar cell installed on a roof, for example.

Claims

1. A solar cell comprising: A light-transmitting first electrode; The second electrode; a light absorbing layer located between the first electrode and the second electrode; and an intermediate layer located between the first electrode and the light absorbing layer, The light absorbing layer contains a fluorine compound and a perovskite compound represented by a composition formula ASnX3, wherein: A is a monovalent cation, X is a halogen anion, The intermediate layer contains at least one selected from metal oxides, metal sulfides, metal chalcogenides and metal nitrides, The upper surface of the intermediate layer is in contact with the lower surface of the light absorbing layer, The concentration of the fluorine compound is high in the lower part of the light absorbing layer, while the concentration of the fluorine compound is low in the upper part of the light absorbing layer. At the interface between the light absorbing layer and the intermediate layer, the molar ratio of fluorine atoms to the perovskite compound is 49% or more, The molar ratio is calculated based on the following formula (1) according to the measurement results obtained by X-ray photoelectron spectroscopy: Molar ratio = (the number of moles of fluorine atoms in the interval d2) / {(the number of moles of halogen anions contained in the perovskite compound in the light absorbing layer) / 3} (1) The interval d2 is the spectral capability of the X-ray photoelectron spectrometer.

2. The solar cell according to claim 1, The intermediate layer is formed of a porous body.

3. The solar cell according to claim 2, At least one selected from the perovskite compound and the fluorine compound is contained in the porous body.

4. The solar cell according to claim 1, The intermediate layer is formed of a dense layer.

5. The solar cell according to claim 1, The intermediate layer functions as an electron transport layer.

6. The solar cell according to claim 1, The molar ratio is 50.2% or more and 66.3% or less.

7. The solar cell according to claim 1, The fluorine compound is SnF2.

8. The solar cell according to claim 1, The invention further includes a hole transport layer located between the second electrode and the light absorbing layer.